2021
DOI: 10.1177/08830738211041824
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Neurologists’ Perspectives on Sexual and Reproductive Health Care for Adolescent and Young Adult Women With Epilepsy and Intellectual Disability

Abstract: Objective: To explore perspectives of pediatric neurologists regarding sexual and reproductive health care for adolescent women with epilepsy (WWE) and intellectual disability. Methods: We interviewed pediatric neurologists regarding sexual and reproductive health for WWE with intellectual disability. We audio-recorded and transcribed interviews and conducted qualitative analysis. Results: 16 pediatric neurologists participated. Themes included the following: (1) Pediatric neurologists have differing perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Overall, these studies showed that women with disabilities were not provided information, or only received partial information, related to the different options of contraception (Alhusen et al, 2020; Beckmann et al, 1989; Horner-Johnson et al, 2022; McCarthy, 2011; Wiseman & Ferrie, 2020), with limited details on how each method could affect their health. Women with disabilities were prescribed longer-term methods of contraception (Agaronnik et al, 2020; Horner-Johnson et al, 2022; Kirkpatrick et al, 2022; Ledger et al, 2016; McCarthy, 2010, 2011; Shiwakoti et al, 2021) and decisions surrounding contraception were often made by people in their social milieu (i.e., caregivers or professionals; Ledger et al, 2016; McCarthy, 2009a, 2009b; Shiwakoti et al, 2021; Wiseman & Ferrie, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, these studies showed that women with disabilities were not provided information, or only received partial information, related to the different options of contraception (Alhusen et al, 2020; Beckmann et al, 1989; Horner-Johnson et al, 2022; McCarthy, 2011; Wiseman & Ferrie, 2020), with limited details on how each method could affect their health. Women with disabilities were prescribed longer-term methods of contraception (Agaronnik et al, 2020; Horner-Johnson et al, 2022; Kirkpatrick et al, 2022; Ledger et al, 2016; McCarthy, 2010, 2011; Shiwakoti et al, 2021) and decisions surrounding contraception were often made by people in their social milieu (i.e., caregivers or professionals; Ledger et al, 2016; McCarthy, 2009a, 2009b; Shiwakoti et al, 2021; Wiseman & Ferrie, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Our collective of multidisciplinary subspecialty clinicians and health services researchers has described some of the common challenges that subspecialists feel undermine their provision of SRH care 4,14,23,24 . Our qualitative research also indicates that many patients with chronic diseases feel that their SRH needs are not met in the current subspecialty care model 25–28 ; they overwhelmingly desire for their subspecialists to address their SRH as it relates to their diseases, but with a holistic approach that accounts for the greater context of their values, preferences, and life circumstances 29,30 .…”
Section: A New Model Is Needed To Provide High‐quality Sexual and Rep...mentioning
confidence: 88%
“…[13][14][15][16][17][18][19][20][21][22] Our collective of multidisciplinary subspecialty clinicians and health services researchers has described some of the common challenges that subspecialists feel undermine their provision of SRH care. 4,14,23,24 Our qualitative research also indicates that many patients with chronic diseases feel that their SRH needs are not met in the current subspecialty care model [25][26][27][28] ; they overwhelmingly desire for their subspecialists to address their SRH as it relates to their diseases, but with a holistic approach that accounts for the greater context of their values, preferences, and life circumstances. 29,30 Herein, we offer a blueprint, based on a person-centered framework, to generate strategies across the subspecialties that better meet the needs of birthing people and enhance their SRH care and outcomes.…”
mentioning
confidence: 91%
“…If, on one hand, a broader literature exists on the negative impact of physiological changes on sexual functioning [32,33] or of lifestyle comorbidities affecting sexual health [7,34,35], on the other hand, little attention has been paid towards the importance of other psycho-relational variables in determining the "functioning" of the elderly person during sexual activity [36]. In fact, contrary to the common occidental point of view regarding the sole existence of penetrative sexual activity [37,38], especially for elderly people, or people belonging to populations with specific needs, such as people affected by intellectual or physical disabilities [39], a broader consideration of sexual activity as an activity characterized by many other behaviours seems to be the best way of thinking. Following this consideration, Muller and colleagues elegantly demonstrated the validity of the so-called "second language of sexuality", that is, the importance of affection for the couple's satisfaction [40].…”
Section: Discussionmentioning
confidence: 99%